Multi-omics analyses reveal altered gut microbial thiamine production in obesity - Xia, Yu; Lu, Longya; Wang, Lulu; Qiu, Yanyan; Liu, Xingyin; Ge, Weihong (Frontiers in Microbiology, 2025)
ObjectiveAccumulating evidence highlights the important role of B vitamins in maintaining the balance of gut microbial ecology and metabolism, however, few studies have focused on changes in B vitamins homeostasis in the gut and their associations with disease. This study aims to investigate the potential interplay between B vitamins, gut microbiota, and obesity.MethodsWe conducted an integrated analysis of fecal shotgun metagenomics, fecal metabolome concerning B vitamins and short chain fatty acids (SCFAs), and obese phenotypes in a cohort of 63 participants, including 31 healthy controls and 32 individuals with obesity.ResultsMetabolomic analysis identified significantly lower levels of fecal thiamine in individuals with obesity (PWilcoxon < 0.001). Fecal thiamine levels exhibited a positive correlation with HDL-C and a negative correlation with BMI, DBP, fasting serum insulin, HOMA-IR, triglycerides, and propionic acid. Binary logistics regression suggested that fecal thiamine deficiency may be a potential contributor to the onset of obesity (Odds ratio: 0.295). Metagenomic analysis indicated that the microbial composition in individuals with obesity was characterized by a predominance of potential opportunistic pathogens, a loss of complexity, and a decrease in thiamine-producing bacteria. Integrated analysis indicated that thiamine deficiency was positively associated with the depletion of thiamine auxotrophic bacteria in the obese microbiome. Functional analysis revealed that KOs content for enzymes involved in the microbial production of thiamine were significantly lower in obesity, including tRNA uracil 4-sulfurtransferase (ThiI, PWilcoxon = 0.001) and nucleoside-triphosphatase (NTPCR, PWilcoxon = 0.006), both of which were positively associated with fecal thiamine.ConclusionOur study highlights the impairment of microbial thiamine production and its broad associations with gut microbiota dysbiosis and obesity-related phenotypes. Our findings provide a rationale for developing treatments that utilize thiamine to prevent obesity by modulating gut microbiota.